Free peritoneal perforation in a patient with Crohn's disease – Report of a case - Leal, Raquel Franco (Elsevier, 2013)
INTRODUCTION: Bowel perforation with free peritoneal air is a rare complication of Crohn's disease (CD). PRESENTATION OF CASE: We report a case of a 36 year-old male patient, with history significant for CD and he presented to the emergency room with a free peritoneal perforation, which was diagnosed by abdominal X-ray and confirmed by CT scan. The patient underwent a laparotomy surgery; however, no site of perforation was identified. The surgical approach was to clean the cavity, close the abdominal wall and administer antibiotic therapy. He demonstrated good early and late postoperative outcomes. DISCUSSION: We report a rare case of free perforation to the peritoneum in a patient with CD. The most likely hypothesis is that it was a micro-colonic perforation. Antibiotic therapy and a conservative surgical approach without colon resection can be performed and it is reported in the literature. CONCLUSION: Emergency conditions in CD may result in significant morbidity, but are normally associated with low mortality, if identified and treated properly.